Contrast materials and contrast reaction management - Onur, Mehmet Ruhi; Dogra, Vikram S. (Springer-Verlag London Ltd, 2013)
The use of contrast materials in radiology has increased in parallel with an ever-increasing number of cross-sectional examinations. Appropriate decisions concerning contrast material administration are based upon two principles: contrast materials should provide marked attenuation differences between unenhanced and enhanced images, and their use should involve as little morbidity as possible. The administration of contrast materials may result in various side effects which range from minor physiological disturbances to severe life-threatening adverse events. Radiologists must be knowledgeable of the adverse effects of all contrast materials, as well as the proper management of these complications. In this chapter we present general information about contrast materials. Adverse reactions of contrast materials and management of adverse reactions are also summarized. © Springer-Verlag London 2013.